New Zealand Austrophthiracarus (Acari, Oribatida, Steganacaridae): two new species from the North Island - Liu, Dong; Zhang, Zhi-Qiang (Zootaxa, 2018)
Two new species of Austrophthiracarus (Oribatida: Steganacaridae) from national parks on the North Island of New Zealand are described: Austrophthiracarus taranaki sp. nov. from moss along tracks in Wilkies Pools, Egmont National Park, Taranaki and Austrophthiracarus whirinaki sp. nov. from litter in Whirinaki Forest, between Rotorua and Taupo. An updated key to all known species of Austrophthiracarus in New Zealand is presented.